Comment on “Potential Evaporation and the Complementary Relationship” by Tu et al. (2023) - Jozsef Szilagyi (Water Resources Research, 2023)
Abstract Thanks to the authors' detailed discussion of the complementary relationship of evaporation and the processes involved, one is compelled to get a clearer picture of how to correctly interpret it.